RESPON PRODUKSI PADI ORGANIK PADA BERBAGAI DOSIS PUPUK KANDANG DAN JUMLAH BIBIT PER LUBANG TANAM - Wira Hadianto; Muhammad Jalil; Jekki Irawan (Jurnal Agrotek Lestari, 2018)
This study aims to determine the effect of dosage of manure and the number of seeds per planting hole on the growth and yield of organic rice crops and the real or not the interaction of these two factors. The experimental design to be used in this research is Split Plot 4 x 3, with 3 replications. Factor dose of manure (D) as main plot consist of 4 level, that is: 0 ton ha-1 (control), 5 ton ha-1, 10 ton ha-1 and 15 ton ha-1. Factor Number of Seedlings per Planting Hole (B) as subplot consists of 3 levels, namely: 1 Seeds per planting hole, 2 Seeds per planting hole and 3 Seeds per hole The study was conducted in Suka Makmue district, Nagan Raya District, Aceh Province. Starting from March to July 2016. The result of dose of manure has a very significant effect on the number of panicles, the effect is not significant on the length of panicle, the percentage of unhulled grain, the percentage of unhulled grain, the weight of 1000 grains, the weight of Grain Contains Per Rumpun and production per hectare. The number of seedlings on cultivation has a significant effect on the number of panicles, panicle length, percentage of unhulled grain, percentage of unhulled grain, weight of 1000 grains, the grain weight and production per hectare. Keywords : Organic Fertilizer, number of seeds per planting hole, rice production